Fourrier Transform Infrared and Gel Permeation Chromatography Evaluation to Prepared Polyurethane Paint from Polyol Palm Oil Based - Teuku Rihayat; . Suryani; Pocut Nurul Alam (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
New emulsion type paint was prepared by utilizing polyol for the production of polyurethane by reaction with an isocyanate was obtained by the synthesis of palm oil-based oleic acid with glycerol. Dodecylbenzene sulfonic acid (DBSA) was used as catalyst and emulsifier. The various methods for preparing Polyurethane /clay Nano composites, but in this research the author choice by a pre-polymer method and were evaluated by Fourier Transform Infrared (FTIR) spectra to determine micro-domain structures of segmented PU. The molecular weight (MW) of polyol was obtained by using gel permeation chromatography (GPC) and the result was about 950. The micro domain structures of the segmented PU were analysed by FTIR by following the work of Seymour et al. to estimate the degree of phase separation in segmented PU. The formation of hydrogen bonding by –C=O group can be determined by examining the peak position at 1709 cm-1 for hydrogen bonded –C=O and at 1731 cm-1 for free –C=O. The molecular weight (MW) of PU based on palm oil was about 3.266. The performance characteristics of materials indicate to be comparable with the corresponding industrial standard